Artropofauna fitófaga y benéfica asociada al cultivo de frutilla (Fragaria x ananassa), Tucumán, Argentina - Gibilisco, Santiago Manuel; Carrizo, Karen G.; Corral, M.N.; Allori Stazzonelli, Enzo; Claps, Lucia Elena; Maza, Noelia; Kirschbaum, Daniel Santiago; Funes, Claudia Fernanda (Facultad de Ciencias Naturales e Instituto Miguel Lillo, Universidad Nacional de Tucumán, 2022)
Poster